„Celestes Camaradas": Samuel Feijóo o la soledad del chamán - Skowroński, Konrad (Studia Romanica Posnaniensia, 2007)
Basing on poetic works of Samuel Feijóo, one of Cuba's most prolific artists of the 20th century, the author of the study tries to establish the symmetries existing between the social position and work of a shaman and a poet. Thereby, the study brings innovatory vision of poetic vocation and practice, hence seen (with some restrictions) as modern form of states and activities that in archaic cultures were those of the shaman. Furthermore, the author exalts the solitude inscribed in life of both poet and shaman and proves that neither the union with landscape nor the suspension of the difference between reality and illusion fits in the Occident scientific language, and they are more likely to be described as transformation of shaman's ecstatic euphoria. Putting those theoretical assumptions into practice, the study presents the interpretation of two poems from Feijóo's first important book of poetry: Camarada Celeste, which are read as transcriptions of ecstatic journey to the Upper World, and of the fragment of poet's masterpiece Beth-el, where we descend with him to the Lower World.